2019
DOI: 10.1002/ijc.32330
|View full text |Cite
|
Sign up to set email alerts
|

Significant inter‐ and intra‐laboratory variation in grading of invasive breast cancer: A nationwide study of 33,043 patients in the Netherlands

Abstract: Accurate, consistent and reproducible grading by pathologists is of key‐importance for identification of individual patients with invasive breast cancer (IBC) that will or will not benefit from adjuvant systemic treatment. We studied the laboratory‐specific grading variation using nationwide real‐life data to create insight and awareness in grading variation. Synoptic pathology reports of all IBC resection‐specimens, obtained between 2013 and 2016, were retrieved from the nationwide Dutch Pathology Registry (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…We demonstrated that there was limited variability in ER, PR, and HER2 positivity rates among pathology departments. Overall positivity rates were 87.9% for ER, 72.8% for PR, and 13.1% for HER2, with a median Ki67 proliferation index of 22% and 51.4% of tumors deemed grade II, which are in line with international findings [ 19 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Although the proportion HER2 positivity ranged from 9.4% to 16.3% (thus varying from 1 positive out of 6 tested patients to 1 positive out of 11 patients tested), the confidence intervals were broadly overlapping for the vast majority of the labs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We demonstrated that there was limited variability in ER, PR, and HER2 positivity rates among pathology departments. Overall positivity rates were 87.9% for ER, 72.8% for PR, and 13.1% for HER2, with a median Ki67 proliferation index of 22% and 51.4% of tumors deemed grade II, which are in line with international findings [ 19 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Although the proportion HER2 positivity ranged from 9.4% to 16.3% (thus varying from 1 positive out of 6 tested patients to 1 positive out of 11 patients tested), the confidence intervals were broadly overlapping for the vast majority of the labs.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, we also demonstrated unacceptable inter- and intra-laboratory variability in histological grade and Ki67 assessment, urging imminent efforts to further standardize testing procedures. In a large study of 33,043 non-selected breast cancer patients, van Dooijeweert et al also demonstrated a substantial variability in histological grading among pathology departments [ 29 ]. It has long been acknowledged that both Ki67 and histological grade provide useful prognostic information [ 30 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion (30–60%) of patients are diagnosed with grade 2 tumours, and in these patients the indication for adjuvant systemic treatment is less clear. Especially in this category of patients, high interobserver grading variability and institutional inconsistencies have been reported 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…There is a connection between the degree of breast cancer and the mutation that caused it ( 40 ). However, enormous differences were found between inter- and intra-laboratory interpretations of the classification of breast cancer ( 41 ).…”
Section: Cancer Related Candidate Genes With Potential Of Ngs Panel Amentioning
confidence: 99%